A New Implantable Closed-Loop Clinical Neural Interface: First Application in Parkinson’s Disease - Arlotti, Mattia; Colombo, Matteo; Bonfanti, Andrea; Mandat, Tomasz; Lanotte, Michele Maria; Pirola, Elena; Borellini, Linda; Rampini, Paolo; Eleopra, Roberto; Rinaldo, Sara; Romito, Luigi; Janssen, Marcus L. F.; et al. (Frontiers in Neuroscience, 2021)
Deep brain stimulation is used for the treatment of movement disorders, including Parkinson’s Disease, Dystonia and Essential tremor, and have shown clinical benefits in other brain disorders. A natural path for the improvement of this technique is to continuously observe the stimulation effects on patient symptoms and neurophysiological markers. This requires the evolution of conventional deep brain stimulators to bi-directional interfaces, able to record, process, store and wireless communicate neural signals in a robust and reliable fashion. Here we present the architecture, design, and first use of an implantable stimulation and sensing interface (AlphaDBSR System) characterized by artifact-free recording and distributed data-management protocols. Its application in three Parkinsonian patients (clinical trial n. NCT04681534) is shown as a proof of functioning of a clinically viable implanted brain computer interface for adaptive deep brain stimulation. Reliable artifact free-recordings, and chronic long-term data and neural signal management are in place.